Association Between Neonatal Jaundice and Maternal Oxytocin Infusion in Albayda Medical Center - Arij Abdelgader; Hibah Mustafa; Ranyia Tayib; Wafa Saed (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. Neonatal jaundice is one of the most widespread clinical conditions, and the most significant condition that need medical attention. The objective of this study was to determine the relationship between the development of neonatal jaundice and maternal oxytocin infusion for initiation of labor. Methods. A prospective case control observational was conducted on 118 neonates with jaundice which followed up for a period of 6 months in the neonatal care unit NCU at Al-Bayda medical center (AMC) – Libya. After exclusion of 20 newborns, the remaining 98 newborns were divided into 2 groups, group A (involve 40 newborns in whom no oxytocin used for mother) and group B (58 newborns were oxytocin used for induction of labour). Results. The results showed that the mean of TSB (total serum bilirubin) in group B (there mothers receive oxytocin to initiate labor) were significantly higher than group A (there mothers didn’t receive oxytocin), where there was 10 out of 58 neonates in group B their TSB above 12mg/dl and only one newborn of the 40 in group A has a reading of TSB above 12 mg/dl. Conclusion. The direct relationship between oxytocin infusion and high-level bilirubin level is hard to confirm in this study because the inclusion of mothers that received oxytocin infusion for induction only. Cite this article: Abdelgader A, Mustafa H, Tayib R, Saed W. Association Between Neonatal Jaundice and Maternal Oxytocin Infusion in Albayda Medical Center. Alq J Med App Sci. 2022;5(2):602-605. https://doi.org/10.5281/zenodo.7464360